(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Task-Based Language Teaching (TBLT) has emerged as a prominent approach in language education, emphasizing the use of authentic tasks to promote language acquisition. However, its implementation is fraught with challenges that can hinder its effectiveness. This article explores key methodological aspects related to these challenges and proposes solutions to enhance the successful integration of TBLT in language classrooms. Through a comprehensive literature review and analysis of current practices, this study identifies common obstacles such as teacher preparedness, learner resistance, and assessment difficulties. It also suggests practical strategies for overcoming these barriers, including professional development for educators, fostering a supportive classroom environment, and developing effective assessment tools. The findings underscore the importance of addressing these challenges to fully realize the potential of TBLT in fostering communicative competence.